2021
DOI: 10.1007/s12032-021-01503-z
|View full text |Cite
|
Sign up to set email alerts
|

The anti-angiogenic agent lenvatinib induces tumor vessel normalization and enhances radiosensitivity in hepatocellular tumors

Abstract: The evaluation of angiogenesis inhibitors requires the analysis of the precise structure and function of tumor vessels. The anti-angiogenic agents lenvatinib and sorafenib are multi-target tyrosine kinase inhibitors that have been approved for the treatment of hepatocellular carcinoma (HCC). However, the different effects on tumor vasculature between lenvatinib and sorafenib are not well understood. In this study we analyzed the effects of both drugs on vascular structure and function, including vascular norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…CT scans showed no significant decrease in the volume density of TBVs at this point. In addition, the authors reported a significant decrease in the volume density of TBVs on day 14 of lenvatinib administration [4]. DOI: 10.1159/000526976 Therefore, we propose that the shrinkage of the TBV diameter that we confirmed in patients over a short period of time may be a process of normalizing the abnormally dilated TBVs.…”
Section: Discussion/conclusionsupporting
confidence: 61%
See 1 more Smart Citation
“…CT scans showed no significant decrease in the volume density of TBVs at this point. In addition, the authors reported a significant decrease in the volume density of TBVs on day 14 of lenvatinib administration [4]. DOI: 10.1159/000526976 Therefore, we propose that the shrinkage of the TBV diameter that we confirmed in patients over a short period of time may be a process of normalizing the abnormally dilated TBVs.…”
Section: Discussion/conclusionsupporting
confidence: 61%
“…Lenvatinib, a multi-tyrosine kinase inhibitor that targets vascular endothelial growth factor receptors (VEGFR) 1–3, fibroblast growth factor receptors (FGFR) 1–3, rearranged during transfection (RET), mast/stem cell growth factor receptor kit (SCFR), and platelet-derived growth factor receptor (PDGFR) beta [ 2 , 3 ], is available for the treatment of unresectable HCC. In vivo studies have shown that lenvatinib strongly inhibits VEGFR and FGFR, resulting in a marked normalization of tumor blood vessels (TBVs) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Recently, Une et al reported that LEN treatment induced vascular normalization and improved the intratumoral microenvironment in HCC tumors earlier and more effectively than sorafenib treatment. 46 This mechanism will improve the distribution of Lipiodol ® mixed in combination with anticancer drugs and enhance the therapeutic effect of TACE. The effectiveness of combination therapy with sorafenib and TACE for HCC has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of angiogenesis by lenvatinib has been shown to result in normalization of tumor vasculature, which may increase delivery and uptake of chemotherapy into cancer cells [ 32 , 33 ]; and in preclinical studies, lenvatinib monotherapy showed activity in chemotherapy-resistant human tumor xenografts [ 34 ]. Chemotherapy has a direct antitumor effect but also has the capacity to promote antitumor immunogenicity via the release of tumor-associated antigens and the maturation of antigen-presenting cells, resulting in activation of cytotoxic T cells ( Figure 1B ) [ 35 , 36 ].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%